MOOCs and personalized massification [Los MOOC y la masificación personalizada] - Valdiviezo Diaz, P. (2014)
Higher education is experiencing a rapid transformation driven by technological development, we headed to a globalization of university in which massification in the Massive Open Courses (MOOC) has found alternatives for academic support through the peer mentoring and teacher's tutoring. One area that will be able to strengthen and expand the tutorials possibilities in a near future is a field of artificial intelligence which has experienced significant developments in recent years; this field is called recommender systems and nowadays you can find important experiences in which, regardless of the number of students, learning processes are served and supported. This article reflects on the potential of artificial intelligence and its role in the development of MOOCs.